Charge accumulation kinetics in multi-redox molecular catalysts immobilised on TiO2. Issue 3 (18th November 2020) - Bozal-Ginesta, Carlota; Mesa, Camilo A.; Eisenschmidt, Annika; Francàs, Laia; Shankar, Ravi B.; Antón-García, Daniel; Warnan, Julien; Willkomm, Janina; Reynal, Anna; Reisner, Erwin; Durrant, James R.
Abstract : Using transient spectroelectrochemical techniques, we investigate multiply reduced states of molecular catalysts on titania photoelectrodes as a function of the applied bias and the light intensity. Abstract : Multi-redox catalysis requires the accumulation of more than one charge carrier and is crucial for solar energy conversion into fuels and valuable chemicals. In photo(electro)chemical systems, however, the necessary accumulation of multiple, long-lived charges is challenged by recombination with their counterparts. Herein, we investigate charge accumulation in two model multi-redox molecular catalysts for proton and CO2 reduction attached onto mesoporous TiO2 electrodes. Transient absorption spectroscopy and spectroelectrochemical techniques have been employed to study the kinetics of photoinduced electron transfer from the TiO2 to the molecular catalysts in acetonitrile, with triethanolamine as the hole scavenger. At high light intensities, we detect charge accumulation in the millisecond timescale in the form of multi-reduced species. The redox potentials of the catalysts and the capacity of TiO2 to accumulate electrons play an essential role in the charge accumulation process at the molecular catalyst. Recombination of reduced species with valence band holes in TiO2 is observed to be faster than microseconds, while electron transfer from multi-reduced species to the conduction band or the electrolyte occurs in the millisecond timescale. Finally, under light irradiation, we show how charge accumulation on the catalyst is regulated as a function of the applied bias and the excitation light intensity.